Research on an Improved Induction Power-taking Method for Smart Grid Monitoring Equipment. Issue 4 (April 2021) - Yang, Mengqin; Yang, Jun
Abstract: The development of smart cities is inseparable from the support of smart grids. Transmission lines are the bloodline of the smart grid. Due to the geographical environment and insulation conditions of the transmission lines, the power supply of its monitoring equipment cannot directly transfer electrical energy from the cable. The low-pressure end is transferred to the high-pressure end. In order to ensure the smooth operation of the smart grid, the development of an online monitoring device that can continue to work reliably in different environments is a prerequisite to ensure the effective operation of the transmission line [1] . Aiming at the technical bottleneck of monitoring equipment, this article improves the conventional induction power extraction method, and proposes an induction power extraction method based on parallel resonance, by matching the capacitor in the secondary winding of the magnetic core with the corresponding excitation inductance, parallel resonance occurs, thereby increasing the equivalent impedance of the damping branch where the magnetic core is located, so that the load can obtain more power through another branch. Finally, an electromagnetic core electromagnetic simulation experiment was carried out by using Ansoft Maxwell simulation software to verify the effectiveness of the method.